2021
DOI: 10.1039/d1ra07022c
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the thermal conductivity of MOF-5 from first principles

Abstract: The mechanism of thermal transport in MOF-5 and the tailoring strategies of thermal conductivity κ via metal substitution and strain engineering were investigated by first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In this context, Figure 3a shows for the prototypical case of IRMOF-1 that the vibrational frequencies at Γ (the center of the first Brillouin zone) in the entire spectral region agree very well between FF and DFT calculations. This agreement is still good when zooming into the low-frequency region, which comprises the phonons that are most important for thermal transport (see Figure 3b) [36]. A similarly good performance of the force fields is observed for the other MOFs, as shown in Figure S4 in the Supplementary Materials.…”
Section: Assessing the Employed Force Fieldssupporting
confidence: 64%
See 1 more Smart Citation
“…In this context, Figure 3a shows for the prototypical case of IRMOF-1 that the vibrational frequencies at Γ (the center of the first Brillouin zone) in the entire spectral region agree very well between FF and DFT calculations. This agreement is still good when zooming into the low-frequency region, which comprises the phonons that are most important for thermal transport (see Figure 3b) [36]. A similarly good performance of the force fields is observed for the other MOFs, as shown in Figure S4 in the Supplementary Materials.…”
Section: Assessing the Employed Force Fieldssupporting
confidence: 64%
“…Conversely, the interpenetration of frameworks results in materials whose thermal conductivities are essentially the sums of those of the sub-systems [34]. Additionally, the impact of phonon scattering rates on the MOFs' thermal conductivities was studied for a variety of MOFs [35][36][37]. Changes in the phonon scattering behavior are also key to understanding variations in thermal conductivities due to different functional groups in the linkers of zeolitic imidazolate framework 8 (ZIF-8) systems [38].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have compared the lattice thermal conductivity of the h-B 3 O nanosheet with that of other porous materials at room temperature. It was found that h-B 3 O has a high lattice thermal conductivity at low temperatures, in particular, its lattice thermal conductivity at room temperature is 46 W m −1 K −1 , which is much higher than that of recently reported porous materials such as g-C 3 N 4 (17 W m −1 K −1 ), 75 COF-1 (1.73 W m −1 K −1 ), 76 MOF-5 (0.33 W m −1 K −1 ), 77 etc. To sum up, our study shows that the h-B 3 O nanosheet has excellent thermal transport properties, which is conducive to the fast adsorption and release of H 2 molecules, and is an excellent candidate for reversible hydrogen storage at ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Lattice dynamics serves as a pivotal component in elucidating the dynamic and thermodynamic properties of materials, including thermal conductivity, thermal expansion, heat capacity, vibrational energy and entropy, and characteristics related to structural phase transformations. The concept of phonons, as an analogue of vibrational modes in molecules, has been introduced as correlated vibrations of atoms in crystalline materials. Phonons are described as collective, quantized lattice vibrations, providing a framework for understanding the dynamics within solid materials .…”
Section: Introductionmentioning
confidence: 99%